2021
DOI: 10.14421/al-bidayah.v12i2.586
|View full text |Cite
|
Sign up to set email alerts
|

Differences In The Reading Comprehension Ability Of Students In The PQ4R Learning Model For Indonesian Language Subjects

Abstract: The purpose of this research is to determine students' reading comprehension skills before and after using the PQ4R learning model. This research was motivated by preliminary studies, which showed that students' reading comprehension skills are still low in conventional learning models. This is a quantitative research consisting of a one-group pretest-posttest research design. Data were obtained from 22 students of state elementary school 03 Sontas using a written test of 6 (six) questions. The research showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
(5 reference statements)
3
1
0
Order By: Relevance
“…With the predetermined condition, the data is considered normally distributed if the sig (2-tailed) value obtained from the results of the calculation is greater than the alpha rate of 5%, or sig (2-tailed) > 0.05. data in the study were distributed normally. We performed a study on the impact of digital museums on reading comprehension skills in the context of theme learning, which is consistent with the research of Rahmawati et al (2018). The study's findings showed that the data were normally distributed, with significant values for the experimental and control classes of 0.200 > 0.05.…”
Section: Findings and Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…With the predetermined condition, the data is considered normally distributed if the sig (2-tailed) value obtained from the results of the calculation is greater than the alpha rate of 5%, or sig (2-tailed) > 0.05. data in the study were distributed normally. We performed a study on the impact of digital museums on reading comprehension skills in the context of theme learning, which is consistent with the research of Rahmawati et al (2018). The study's findings showed that the data were normally distributed, with significant values for the experimental and control classes of 0.200 > 0.05.…”
Section: Findings and Discussionsupporting
confidence: 83%
“…In line with the research conducted by Sri Rahmawati (2018) on the Influence of Digital Museums in the Context of Reading Comprehension Ability in Learning history. The results of the study obtained a pretest value of t Sig.…”
Section: Findings and Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Some of the difficulties faced by students in Indonesian language content, especially story reading skills, include students needing help to understand linguistic and non-linguistic aspects in reading stories, students need help with motivational encouragement in story reading activities both from providing examples and practice, students need learning media that supports the learning activity of reading stories (Rahmawati et al, 2021;I. F. R. Sari, 2018).…”
Section: Introductionmentioning
confidence: 99%